(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information about the “Katta Ashula” direction and about the great Margilon singers: Boltaboi Radjabov, Mamatbobo Satorov, Dzhorakhan Sultanov, Mamurjon Uzokov.